DEVELOPMENT OF TRANSFER PRICING REGULATIONS IN INDONESIA - Saragi, Daniel Edgar Hirasma (EP FEB UNS, 2024)
This research driven by the urgency to understanding the massive improvement of transfer pricing regulations in Indonesia. Directorate General of Taxes (DGT) have adjusted along with the advancement of macroeconomic, business field, cross border trade, and domestic needs. This study aims to describe the development of transfer pricing regulations in Indonesia, since it was first enacted in 1983. The analysis covers three main topics, which are the implementation and examination of arm's length principle, transfer pricing documentation, and advance pricing agreement. This research used qualitative methodology, particularly analytical descriptive approach. Analytical descriptive performed by analyze, capture, and summary a set of regulations, then provide them in the text containing important provision from each regulation. The result shows that there has been a significant development in transfer pricing regulation in Indonesia. Since the first time enacted, there are eight regulations concerning arm’s length principle, three regulations concerning TP Doc, and five regulations concerning advance pricing agreement which enacted sequentially. Those have provided more detailed rules and fulfilled stakeholders' needs. Novelty of this research can be seen through the comprehensive inventory of transfer pricing regulations in Indonesia, which can provide broad explanation for readers. This research may contribute to enrich the transfer pricing literature for academics. Besides, by describe the whole transfer pricing regulations in Indonesia, this research may also contribute to broaden taxpayer’s understanding and improve service quality of tax authority. From this research, it can be concluded that development of the transfer pricing regulations has provided legal certainty and efficiency for taxpayers and DGT in its implementation.